Deteksi virus avian influenza (H5N1) pada unggas air dengan uji Haemagglutination Inhibition (HI) dan Reserse Transcriptase-Polymerase Chain Reaction (RT-PCR) di Propinsi Lampung - D.D. Putri; E. Handharyani; R.D. Soejoedono (Hemera Zoa, 2009)
The objective of this research is to examine the presence of antibody of avian influenza (AI) H5 and detection of genetic material the subtype of AI virus (H5N1) in waterfowls in Lampung Province. Samples consisted of 673 serum and 673 cloacal swabs, and collected from water fowls Epidemiologycally, samples collection were performed by using multistage sampling method. Examination of AI antibodies by Haemagglutination Inhibition test (HI test) demonstrated that H5 antibodies were found at all district in Lampung Province. High frequency of antibodies were noted at district ofo Tulang Bawang (69.41%). The average of antibody titres of AI were low (under 24) and the lowest antibody titre was found at district of Tulang Bawang (20.92). Evaluation of genetic material H5N1 individually by using Reverse Transcriptase – Polymerase Chain Reaction (RT-PCR) was not found among water fowls. The results showed H5 and unknown N subtype (H5Nx); the second subtype was unknown H and N1 (HxN1). Key words: Avian Influenza, Haemagglutination Inhibition (HI), Reverse Transcriptase Polymerase Chain Reaction (RT-PCR)